MicroRNA-224 is associated with colorectal cancer progression and response to 5-fluorouracil-based chemotherapy by KRAS-dependent and -independent mechanisms - Amankwatia, E B (Br J Cancer, 2015)
BACKGROUND: Colorectal cancers arise from benign adenomas, although not all adenomas progress to cancer and there are marked interpatient differences in disease progression. We have previously associated KRAS mutations with disease progression and reduced survival in colorectal cancer patients. METHODS: We used TaqMan low-density array (TLDA) qRT–PCR analysis to identify miRNAs differentially expressed in normal colorectal mucosa, adenomas and cancers and in isogeneic KRAS WT and mutant HCT116 cells, and used a variety of phenotypic assays to assess the influence of miRNA expression on KRAS activity, chemosensitivity, proliferation and invasion. RESULTS: MicroRNA-224 was differentially expressed in dysplastic colorectal disease and in isogeneic KRAS WT and mutant HCT116 cells. Antagomir-mediated miR-224 silencing in HCT116 KRAS WT cells phenocopied KRAS mutation, increased KRAS activity and ERK and AKT phosphorylation. 5-FU chemosensitivity was significantly increased in miR-224 knockdown cells, and in NIH3T3 cells expressing KRAS and BRAF mutant proteins. Bioinformatics analysis of predicted miR-224 target genes predicted altered cell proliferation, invasion and epithelial–mesenchymal transition (EMT) phenotypes that were experimentally confirmed in miR-224 knockdown cells. CONCLUSIONS: We describe a novel mechanism of KRAS regulation, and highlight the clinical utility of colorectal cancer-specific miRNAs as disease progression or clinical response biomarkers.